TINJAUAN KETEPATAN PENGGUNAAN OAINS PADA PASIEN REUMOTOID ARTHRITIS DI PUSKESMAS AUR DURI KOTA JAMBI TAHUN 2018 - yuli, yuli mudia sari (Universitas Bhakti Kencana, 2020)
Reumotoid arthritis (RA) is an autoimmune disease that is associated with progressive disability, systemic complications and premature death. RA is thought to be a result of dysrelation of the body’s immune system so that it manifests systemically. NSAIDS are used as an initial fix for RA, inappropriate use of NSAIDS can cause gastrointestinal.the purpose of this study was to determine the use of NSAIDS in rheumatic arthritis pattients at Aur Duri Health Center in Jambi City in 2018 namely, the right indication, the right dose, the right frequency, and the potential for drug interactions. Evaluation of the use of these drugs is a quality assurance process in the use of drugs in the Community Health Center which is intended to ensure the drugs are used appropriately, safely effectively.this study was a non-experimental type of research,retrospective data collection by looking at RA medical record data inclluding medical records, sex, age, drug and dosage used and analyzed descriptively. Sampling as many as 132 patients by purposive sampling method. The results showed that there were 132 sampels that met the inclusion and exclusion criteria. Where the most widely used NSAID drugs are profen mothers with an amount of 32,57%, the right indication 100% ,the right dose of the drug with the amount of 100%, the right frequency of the drug with the amount of 100%, the potential for drug interactions minor severity levels 5,30%, severity moderate 32,57% and no interaction 62, 12%. From 132 data of reumotoid arthritis patients at Puskesmas Aur Duri in Jmbi City, the use of NSAID drugs is rational.